Why follow? The interplay of leader categorization, identification, and feeling respected. (January 2013) - Van Quaquebeke, Niels; Eckloff, Tilman
Guided by both social cognitive and identity-based perspectives of leadership, the present study investigated how and when the process of leader categorization results in greater leader effectiveness. Specifically, we propose that the relationship between leader categorization and subordinates' openness toward leadership should be partially mediated by subordinates' identification with their leaders. Furthermore, seeking to corroborate that the issue of self-esteem is the central ingredient in the identification process, we argue that the mediation should become weaker the more subordinates feel that they are being treated disrespectfully by their leaders, and thus are explicitly undermined in their efforts toward self-enhancement. The proposed mediating effect was tested and supported in two field studies ( N 1 = 244, N 2 = 645). In the second study, we also tested and found support for the proposed moderated mediation model. The theoretical and managerial consequences are discussed.